Highly Improved Microwave Absorbing and Mechanical Properties in Cold Sintered ZnO by Incorporating Graphene Oxide. Issue 3 (March 2022) - Gao, Jie; Ding, Qi; Yan, Peng; Liu, Yongping; Huang, Jilong; Mustafa, Tufail; Guo, Rui; Lu, Xueping; Wang, Kangjing; Sun, Shikuan; Feng, Xiaopeng; Luo, Wei; et al.
Highlights: Graphene oxide/ZnO ceramic composites with highly preserved pristine structure of filler are prepared via cold sintering technology. Moderate complex permittivity and good impedance matching lead to highly improved microwave absorbing performance in cold sintered composites compared to the spark plasma sintered ones. Both flexural strength and hardness of the graphene oxide reinforced composites are enhanced remarkably compared to the cold sintered pure ZnO. Abstract: The abruptly increased dielectric loss in graphene oxide (GO) induced by high-temperature sintering has prevented GO from being used as an absorbent in ceramic-matrix microwave absorbing composites (MACs). Here, we show the first example that the pristine structure of GO can be largely preserved in ceramic composite by using cold sintering technology. Compared with the composites densified by ordinary spark plasma sintering, cold sintered samples possess lower complex permittivity and superior impedance matching. Therefore, the cold sintered ZnO composite with 0.50 wt% GO loading shows the minimum reflection loss of -47.5 dB at thickness of 3.2 mm, and the effective absorption bandwidth of 4.4 GHz at thickness of 1.7 mm. Moreover, both flexural strength and hardness of the cold sintered composite are improved considerably compared to the monolithic cold sintered ZnO. These findings imply that cold sintering enables the thermally unstable materials to be applied in highly effective MACs with robust mechanical performance.